Translating the Word, Translating the World: A Closer Look into Translation in Adult Education Research - Ramazan Gungor; Fred M. Schied (Adult Education Research Conference, 2008)
This paper outlines a proposed approach to the issue of translation in the instrument adaptation process in adult education field, and describes a design ensuring effective use of translators to achieve a translation that is appropriate and adequate for a given task.